A new species of Phytoecia (Neomusaria) Plavilstshikov, 1928 from Armenia and a new species of Phytoecia (Parobereina) Danilevsky, 2018 from Iran (Coleoptera, Cerambycidae) - Danilevsky, Mikhail (Zootaxa, 2020)
Phytoecia (Neomusaria) kazaryani sp. nov. similar to Ph. (N.) suvorowi Pic, 1905 is described from Armenia; Phytoecia (Parobereina) kashanica sp. nov. similar to Ph. (P.) vittipennis Reiche, 1877 is described from Iran.